2020
DOI: 10.3390/jcm9041174
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Expected Survival in Men and Women after Suffering a STEMI

Abstract: Introduction: Mortality caused by ST elevation myocardial infarction (STEMI) has declined because of greater use of primary percutaneous coronary intervention (PCI). It is unknown if patients >75 have similar survival as peers. We aim to know it stratifying by sex and assessing how the sex may impact the survival. Methods: We retrospectively selected all patients >75 who suffered a STEMI treated with primary PCI at our institution. We compared their survival with that of the reference population (general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…However, one-year and long-term mortality is controversial. Pascual reported that gender difference is not a risk factor for one-year mortality in STEMI patients [ 46 ], which was supported by the present study results. However, other reports have revealed higher one-year mortality in women compared to men, which is explained by the worse clinical profile and the reduced rate of reperfusion therapy [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one-year and long-term mortality is controversial. Pascual reported that gender difference is not a risk factor for one-year mortality in STEMI patients [ 46 ], which was supported by the present study results. However, other reports have revealed higher one-year mortality in women compared to men, which is explained by the worse clinical profile and the reduced rate of reperfusion therapy [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women with ACS in comparison to men had been at a higher risk for poor clinical outcomes following PCI, particularly in the short-term follow-up period after primary PCI [18,19]. However, the exact mechanisms of these sex-specific differences remain unclear and are probably multifactorial [20].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical process comparing the survival rate of patients experiencing premature STEMI with that of the general population of the same sex, age, and region was calculated as reported elsewhere [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%